Assurance versus frustration: a retrospective single-center analysis of female patients with acute telogen effluvium - Erkin Pekmezci (Sociedade Portuguesa de Dermatologia e Venereologia, 2024)
Objective: Acute telogen effluvium (ATE) is a scalp hair disorder featured by diffuse, non-scarring shedding with higher female predilection. In general, the disorder is perceived as extremely frightening and urges the patient to visit a physician immediately. We retrospectively analyzed the 3-month prognosis of the female patients with hair loss complaint. Methods: Two-hundred and sixty-six female patients who were referred to our hospital with ATE were retrospectively recruited. The patients were analyzed for serum iron, iron-binding capacity, vitamin B12, folate, thyroid-stimulating hormone, and prolactin values. All were prescribed standard zinc and vitamin E supplements in addition to needed medications and invited to a second visit after 3 months. Results: All of the mean values for all parameters were found in normal ranges. Two hundred and nine patients came to the second visit after the 3-month treatment period. Of these patients, 9.1% stated hair shedding ceased completely, 74.6% diminished to some extent, and 16.3% continued as before. Conclusions: Mainly due to normal mean values, none of the analyzed parameters can be accused as the cause of hair sheddings. The frustrations of the patients are so great that it is reasonable to prescribe some supplements, at least for their placebo effects. Treatment for ATE is primarily reassurance and counseling.